Food Security in Acajete, Veracruz - Rivera-Barragán, María Del Rosario; Sánchez-Domínguez, Talia; Corona-Morales, Alep Alejandro (Horizonte Sanitario, 2018)
Objective: To determine the dietary diversity, the level of food security and its relationship with living conditions in families in Acajete, Veracruz. Materials and methods: Proportional stratified sampling, with 95% confidence, 5% error, and 50% response distribution. Household selection was made randomly, resulting in 211 dwellings as a sample. Results: Marginal food security with 40.3% (n = 85), followed by 32.7% of families with food security (n = 69). Regarding the nutritional status of surveyed people, the mode and median was normal weight (57.7%), overweight and obese 25.5% and underweight 16.8%. 33.6% of the people consume three food groups throughout the day, 27.5% four groups, 15.2% two groups, and the same percentage five food groups. There were significant differences (p=0.039) between the education level of the respondents in relation to their food security status, where 84.2% of the illiterate population has some degree of food insecurity, and 15.8% are in Food security. Conclusions: The housing characteristics considered in this study are not a determinant risk factor for Food Insecurity; no significant differences were found with overcrowding (p=0.239), housing ownership (p=0.987); and an unsafe source of drinking water (p = 0.973). The average scores of the Mexican Food Security Survey (EMSA) were statistically significant, therefore it is observed that lower food diversity results in lower food security. The inhabitants of Acajete who are in low or very low food security, only feed on two food groups: cereals or tubers; and legumes, nuts or seeds. When there is marginal food security add meat or fish.